Lectotypification of the name Androsace mathildae Levier (Primulaceae) - Bartolucci, Fabrizio; Conti, Fabio (Phytotaxa, 2019)
Androsace mathildae Levier (1877: 43) is endemic to Abruzzo (central Italy; Bartolucci et al. 2017, 2018), occurring in the Gran Sasso and Monti della Laga national Park (Conti & Bartolucci 2016) and in the Majella national Park (F. Conti and collaborators, submitted), on limestone rocks and screes between 2,350 and 2,900 m a.s.l. This species is listed in Annexes II and IV of the Habitats Directive 92/43/ECC (Rossi et al. 2016), and, according to the IUCN criteria, is evaluated as Least Concern (LC; Rossi et al. 2013, Orsenigo et al. 2018). Androsace mathildae is also included in the project LIFE15 NAT/IT/000946 “Safeguard and valorization of the plant species of EU interest in the Natural Parks of the Abruzzo Apennine” (Di Martino et al. 2016).The present contribution is part of an ongoing project promoted by the Italian Botanical Society aimed at recognizing and typifying all the taxa described from Italy, in order to increase their systematic knowledge and promote further studies (Domina et al. 2012, Passalacqua et al. 2014, Peruzzi et al. 2015, Brundu et al. 2017). The name Androsace mathildae, to the best of our knowledge, was not yet typified (Peruzzi et al. 2015).